P73 THE ASSESSMENT OF PULMONARY ARTERY STIFFNESS IN COPD USING CARDIAC MRI THE Q/A METHOD - Nichola Gale; Sujoy Saikia; Margaret Munnery; John Cockcroft (Artery Research, 2017)
Background: Pulmonary artery distensibility and pulsatility has been studied in patients with COPD using cardiac MRI (CMRI) (1). However, pulmonary artery pulse wave velocity (PA- PWV) using ‘QA’ method (2) in CMRI has not been studied in this population. We hypothesized that patients with COPD have a higher PA-PWV compared to healthy individuals. Methods: This analysis includes 23 COPD and 12 healthy volunteers (current or ex-smokers free from respiratory disease). Cardiac MRI was used to measure PA-PWV using a 3.0T GE Signa HDx MRI scanner (GE Healthcare), phase-contrast cross-sectional images using steady-state free precession sequence were obtained approximately 2 cm above the pulmonary valve, under free-breathing conditions. Aortic PWV was measured using the Sphymocor device along with mean arterial pressure (MAP), heart rate, lung function (forced expiratory volume in 1sec (FEV1) and forced vital capacity (FVC) and their ratio), 6-minute-walk-distance (6MWD) oxygen saturations. Results: Patients with COPD and the healthy individuals were similar in age, gender and BMI (p > 0.05). Patients with COPD had greater PA-PWV and heart rate as well as poorer lung function and oxygen saturations and 6MWD (all p < 0.05) (Table-1). PA-PWV did not relate to age, BMI, AoPWV, MAP, heart rate, lung function, oxygen saturations, but PAPWV was greater in males than females (p < 0.05).